The Effect of Liquidity, Leverage, Profitability, and Company Size on Financial Distress (Case Study of Manufacturing Companies in Various Industrial Sectors Listed on the Indonesian Stock Exchange for the Period 2021-2023) - Nais Zahrotul Aulia; Fauzan, Fauzan (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the impact of liquidity, leverage, profitability, and firm size on financial distress in manufacturing companies within the miscellaneous industry sector listed on the Indonesia Stock Exchange during the period from 2021 to 2023. Financial distress is a condition that threatens the survival of a company, making it essential to identify the influencing factors. The research employs a quantitative approach with purposive sampling, involving 81 companies as samples. Secondary data were collected from the companies’ annual financial reports, and data analysis was conducted using multiple linear regression with SPSS version 25. The results indicate that liquidity and firm size positively influence financial distress, meaning that higher liquidity and larger firm size increase the risk of financial difficulties. Conversely, leverage has a negative effect, suggesting that higher debt levels tend to reduce this risk. Profitability does not have a significant impact. These findings provide valuable insights for management and investors in managing financial risks and preventing bankruptcy. The results can also serve as a basis for formulating effective financial strategies. However, this study has limitations in its sector coverage, being limited to the miscellaneous manufacturing sector, which may restrict the generalizability of the findings to other sectors.